The boundaries of the law: can US private enforcement discipline foreign firms? - Massa, Massimo; Wang, Xiaoqiao; Zhang, Bohui; Zhang, Hong (Journal of International Business Studies, 2025)
Existing studies tend to focus on how a legal system reinforces the efficiency of its domestic firms or foreign companies that are subject to its domestic jurisdiction (e.g., via cross-listing). Our study provides critical normative implications in the era of financial globalization by showing that the influence of a country’s legal institutions extend beyond its territorial boundaries. We examine whether US shareholder-initiated class action lawsuits can discipline non-US firms. Using an international sample of firms over the period 1994–2019, we find that a US class action lawsuit against a non-US firm cross-listed in the US negatively affects the value of its non-US-listed industry peers. The effect is robust in both event-based analyses for short-term market reaction and stacked difference-in-difference analyses for long-term valuation. We uncover two economic mechanisms underlying this effect: information sharing and policy coordination between the US and the non-US firm’s home country. Specifically, the cross-border disciplining effect is more pronounced for firms from countries that lack information and that coordinate with the US at the policy level. Moreover, non-US peer firms subsequently improve their governance practices and financial policies to restore shareholder value. Our findings suggest that private enforcement in the US has a worldwide influence.